ChemInform Abstract: Regioselective Palladium‐Catalyzed Ring‐Opening Reactions of C1‐Substituted Oxabenzonorbornadienes. Issue 10 (March 2015) - Raheem, Mohammed Abdul; Edmunds, Michael; Tam, William
Abstract Palladium‐catalyzed ring‐opening reactions of C1‐substituted oxabenzonorbornadienes with aryl iodides are studied.